THE ROLE OF EUPHEMISMS IN INFORMATION PROGRAMS ACROSS DIFFERENT LINGUISTIC SYSTEMS (A CASE STUDY OF RUSSIAN, UZBEK, AND ENGLISH LANGUAGES) (TAMADDUN NURI JURNALI, 2025)
The article examines the role of euphemisms in Russian, Uzbek, and English-language informational programs, focusing on the methods of softening, concealing, or reframing sensitive or controversial information through linguistic tools. By comparing examples from various news programs, the study identifies similarities and distinctive features in the use of euphemisms across these languages and media contexts.